1995
DOI: 10.1002/jso.2930580205
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule and perineural invasion in gallbladder cancer

Abstract: To clarify the role of neural cell adhesion molecule (NCAM) in perineural invasion, NCAM expression was studied by immunohistochemical staining in 26 cases with gallbladder cancer. In gallbladder cancer, the incidence of perineural invasion and that of positive NCAM expression was 42% and 31%, respectively, which are less frequent than those of bile duct cancer in our previous report. Perineural invasion was observed in 88% of the patients with positive expression of NCAM and in 22% of those with negative expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 9 publications
(10 reference statements)
1
25
0
Order By: Relevance
“…Correlation between N-CAM expression and perineural spread has been confirmed in a variety of human carcinomas. The existence of the polisialiated form of NCAM in Wilms' tumor, neuroblastoma, pituitary tumor, small cell lung cancer, gallbladder and bile duct cancer, squamous cell cancer of head and neck, and prostat cancer results in perineural invasion and agrressive metastatic behaviour with a poor clinical outcome [20][21][22][23][24][25][26][27][28] . As the expression of the polisialiated form of NCAM correlates with tumor growth and invasiveness because of its role in cell disassociation, ıt was considered to be a poor prognostic criterion in pituitary tumors and rhabdomyosarcoma [22,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between N-CAM expression and perineural spread has been confirmed in a variety of human carcinomas. The existence of the polisialiated form of NCAM in Wilms' tumor, neuroblastoma, pituitary tumor, small cell lung cancer, gallbladder and bile duct cancer, squamous cell cancer of head and neck, and prostat cancer results in perineural invasion and agrressive metastatic behaviour with a poor clinical outcome [20][21][22][23][24][25][26][27][28] . As the expression of the polisialiated form of NCAM correlates with tumor growth and invasiveness because of its role in cell disassociation, ıt was considered to be a poor prognostic criterion in pituitary tumors and rhabdomyosarcoma [22,29] .…”
Section: Discussionmentioning
confidence: 99%
“…As vascular and neural infiltrations are known to be ominous prognostic factors, their identification has great clinical relevance. Increasing evidence shows that perineural invasion or the neural cell adhesion molecule might be a prognostic factor for various cancers, such as bile duct cancer (Seki et al 1993, Kayahara et al 1994, gallbladder cancer (Seki et al 1995), breast cancer (Lo et al 1997), esophageal cancer (Tanaka et al 1998), pancreatic cancer (Pour et al 2003, Levy et al 2006, Kayahara et al 2007, prostate cancer (Li et al 2003), and colorectal cancer (Gavert et al 2005, Zhou et al 2009, Li et al 2011. Importantly, a recent report has shown that the severity of the neural invasion in rectal adenocarcinoma is an important factor in a scoring system to assess the prognostic value, showing high correlation with localization and severity (Ceyhan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These studies are based on correlations between NCAM1 expression in cancer cells, as seen in histologic specimens, and perineural invasion (29)(30)(31)(32)(33). Elevated NCAM1 expression has also been reported in nerves at sites of perineural invasion (48).…”
Section: Ncam1 Expression In Schwann Cells Promotes Perineural Invasionmentioning
confidence: 99%
“…NCAM1 expression has been correlated with the presence of perineural invasion in specimens from a variety of cancers (28)(29)(30)(31)(32)(33)(34) and has been reported to play a role in cancer progression and axon guidance (35)(36)(37)(38)(39)(40)(41). Three different shRNAs targeting NCAM1 (referred to herein as sh 1, sh 2, and sh 3, respectively) were used to generate stable cell lines in HEI-286 Schwann cells, and Western blot and immunofluorescence analysis revealed that sh 1 and sh 2 caused strong depletion, while sh 3 led to intermediate depletion of the 140-kDa NCAM1 isoform ( Figure 9A and Supplemental Figure 7A).…”
Section: Depletion Of Ncam1 In Schwann Cells Decreases Cancer Cell Inmentioning
confidence: 99%